Personal and professional perspectives on advance care planning among palliative care staff: An observational study - Tadhg Gleeson; Regina McQuillan; Monika Pilch (Journal of Health Psychology, 2026)
Advance care planning enables individuals to communicate future healthcare preferences, yet engagement remains low internationally. This cross-sectional quantitative study with a qualitative component examined advance care planning engagement among 105 Irish palliative care professionals for themselves, their loved ones, and patients, and associations with psychological factors. Engagement differed across contexts, with greater engagement for patients than for loved ones or themselves (Kendall’s W = 0.356). Fear of death was weakly negatively associated with engagement for loved ones and patients, while palliative care self-efficacy was positively associated with patient-focussed engagement and was its only significant predictor ( R 2 = 0.174). Qualitative responses suggested advance care planning was viewed as a professional responsibility rather than a personal priority. Psychological factors associated with advance care planning engagement may differ across relational contexts, warranting research into underlying barriers. These findings highlight the importance of supporting palliative care professionals’ personal engagement with advance care planning alongside clinical practice.